2011
DOI: 10.1038/nm.2490
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating healthy tissue regeneration by targeting the 5-HT2B receptor in chronic liver disease

Abstract: Tissue homeostasis requires an effective, limited wound-healing response to injury. In chronic disease, failure to regenerate parenchymal tissue leads to the replacement of lost cellular mass with a fibrotic matrix. The mechanisms that dictate the balance of cell regeneration and fibrogenesis are not well understood 1 . Here we report that fibrogenic hepatic stellate cells (HSCs) in the liver are negative regulators of hepatocyte regeneration. This negative regulatory function requires stimulation of the 5-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 31 publications
7
169
0
3
Order By: Relevance
“…Results are expressed as relative expression, which indicates HTR2B mRNA levels relative to GAPDH mRNA levels. activation in cardiomyocytes and hepatic stellate cells (41,42), and they also fit with the ability of 5HT and BW723C86 to increase the activity of ERK1/2-regulated transcription factors that control macrophage activation and polarization (AP-1, C/EBP, SRF) (Supplemental Fig. 3).…”
Section: Ht and 5ht 2b Receptor Engagement Trigger Intracellular Sigsupporting
confidence: 58%
See 1 more Smart Citation
“…Results are expressed as relative expression, which indicates HTR2B mRNA levels relative to GAPDH mRNA levels. activation in cardiomyocytes and hepatic stellate cells (41,42), and they also fit with the ability of 5HT and BW723C86 to increase the activity of ERK1/2-regulated transcription factors that control macrophage activation and polarization (AP-1, C/EBP, SRF) (Supplemental Fig. 3).…”
Section: Ht and 5ht 2b Receptor Engagement Trigger Intracellular Sigsupporting
confidence: 58%
“…Although 5HT controls important functions in the CNS, recent advances have now shown that 5HT functions as a regulator of cell proliferation as well as inflammation, tissue regeneration, and repair (12,42,43). The importance of macrophage polarization for an adequate regulation of these latter processes justifies the presence of functional 5HT receptors on their cell membrane and the 5HT ability to modulate macrophage effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…1b) compared with untreated cells. Incubation of cells with the 5-HT 2B receptor antagonist SB204741 [32] (1 μmol/l) decreased expression of the receptor when compared with untreated cells ( Fig. 1c; n = 3, p = 0.0003).…”
Section: Resultsmentioning
confidence: 93%
“…Of interest, Authors also reported that the use of 5-HT2 receptor-selective antagonists resulted in inhibition of HSC proliferation and in the induction of apoptosis, a relevant issue from a therapeutic point of view. The same group provided another interesting study that revealed a major role for 5-HT2B receptor on HSC-derived myofibroblasts: signaling through this receptor has been described to be able to promote fibrogenesis and, at the same time, to contribute to impair regeneration in a diseased liver [151]. Unequivocal evidence was provided in the latter study by using 5-HT2B knockout mice or specific pharmacological antagonists of 5-HT2B, both procedures resulting in stimulation of proliferation and suppression of fibrosis in different experimental models of CLD.…”
Section: Natural Killer and Natural Killer T Cells In Liver Fibrogenementioning
confidence: 99%